Obedience Pressure and Audit Judgment: Does The Auditor Personality Have A Role? - Suryarini, Trisni; Yulianto, Agung; Shovuro, Shova; Widiatami, Anna Kania (Universitas Swadaya Gunung Jati, 2022)
AbstractThe purpose of this research is to analyze the effect of obedience pressure toward audit judgment by using personality as a moderating variable. This study collect data using a questionnaire on 56 respondens from external auditors in BPK (Audit Board) Representative of Central Java, Indonesia. The method of analysis in this research used Moderating Regression Analysis. The result of this research showed that obedience pressure has a negative effect on audit judgment. Moreover, it was determined that three of the personality traits,Â namely openness to experience, conscientiousness, and neuroticism have significant effects on the relationship between obedience pressure and audit judgment. However other personality traits, that is extraversion and agreeableness do not have significant effects on the relationship between obedience pressure and audit judgment. Based on the results, the relationship between obedience pressure and audit judgment is affected by openness to experience, conscientiousness, and neuroticism.AbstrakTujuan dari penelitian ini adalah untuk menganalisis pengaruh tekanan ketaatan terhadap audit judgment yang dimoderasi oleh sifat kepribadian auditor. Paper ini menggunakan kuesioner untuk mengumpulkan data primer dari 56 responden yang merupakan auditor pada Badan Pemeriksa Keuangan (BPK) Perwakilan Jawa Tengah, Indonesia. Metode analisis dalam penelitian ini ketaatan berpengaruh negatif terhadap audit judgment. Selain itu, dari tiga sifat kepribadian auditor, yaitu keterbukaan terhadap pengalaman, kesadaran, dan neurotisisme memiliki pengaruh yang signifikan terhadap hubungan antara tekanan ketaatan dan audit judgment. Namun ciri-ciri kepribadian lainnya yaitu extraversion dan agreeableness tidak berpengaruh signifikan terhadap hubungan antara tekanan ketaatan dan audit judgment. Secara keseluruhan, hubungan antara tekanan ketaatan dan audit judgment dipengaruhi oleh sifat kepribadian openness to experience, conscientiousness, dan neuroticisme.